PERFORMANCE ANALYSIS OF SECURITY MEASURES IN NEAR FIELD COMMUNICATION - A. Mohammed, Mohammed (My University, 2014)
Nowadays near field communication are largely used in so many different applications for the convenience and ease of use they provide. They store and exchange many personal data, some of them requires more security than others, due to the value they poses, such as banking information and personal identification. And maintaining high level of security is task of the utmost priority. The main focus of this thesis is establishing a knowledge base for different NFC/RFID devices. Evaluating the different encryption algorithms used currently, based on their encryption/decryption time, their immunity to brute force attack, and the amount of power needed to execute them. The encryption algorithms will be implemented using Python programing language and tested on a windows computer in order to test their immunity against brute force attack. Encryption/decryption time and the power usage will be tested on a Raspberry Pi, for the similarities it has with modern mobile devices.
Keywords: Encryption; Decryption; Brute Force Attack; NFC; Security.; fi=Tietoliikennetekniikka|en=Telecommunications Engineering|; fi=Master's Degree Programme in Telecommunication Engineering|en=Master's Degree Programme in Telecommunication Engineering|